Beyond Defeat: Understanding Educators’ Experiences in the 2018 Oklahoma Walkouts - Dyke, Erin; Anderson, Heather; Brown, Autumn; El Sabbagh, Jinan; Fernandez, Hannah; Goodwin, Stacey; Hickey, Mark; Lowther, Jennie; Price, Stephanie; Ruby, Megan; Self, Kristy; Williams, Debbie; et al. (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2022)
As a research team, we collected 40 oral history interviews with teachers and support professionals across the state who meaningfully participated in the 2018 Oklahoma education walkouts. The teachers and staff we interviewed are voices not previously cited in local or national news or would be identified readily as prominent or powerful leaders in the strike -- they are everyday folks, like many of the co-authors, whose vision and critical labor made the strike happen. Our collective analysis illuminates the limits in framing the event narrowly in terms of win-lose or as an anomalous event that began overnight with a statewide Facebook group in March and ended April 12th, when schools reopened. Instead, we draw from our interviews to suggest a framing that centers a constructively critical and in-depth understanding of what educators, students, and their communities collectively began and continue to learn and create in preparation for, during, and in the afterlife of the strike. At the same time, we work to understand in our analysis when and how such collective grassroots work was stalled or challenged. Further, we suggest analyses of the historic event should be more discerning of who speaks for the state’s educators and, alternatively, whose voices and perspectives exist only at the margins of the public record, if at all.